Infective endocarditis in patients with heart transplantation. (1st April 2021) - Martínez-Sellés, Manuel; Tattevin, Pierre; Valerio-Minero, Maricela; de Alarcón, Arístides; Fariñas, M. Carmen; Mirabet-Pérez, Sònia; Lavie-Badie, Yoan; Ambrosi, Pierre; Chabanne, Céline; Duval, Xavier; Lecomte, Raphaël; López-Vilella, Raquel; et al.
Abstract: Background: The incidence of nosocomial and health care-related infective endocarditis (IE) is increasing. Heart transplantation (HT) implies immunosuppression and frequent health care contact. Our aim was to describe the current profile and prognosis of IE in HT recipients. Methods: Multicenter retrospective registry-based study in Spain and France that included cases between 2008 and 2019. Results: During the study period, 8305 HT were performed in Spain and France. We identified 18 IE cases (rate 0.2%). Median age was 57 years; 12 were men (67%). Valve involvement did not have a predominant location and three patients (16.7%) had atrial or ventricular vegetations without valve involvement. The median age-adjusted Charlson index was 4 (interquartile range 3–5). Eleven IE cases (61%) were nosocomial/health care-related. Median time (range) between HT and development of IE was 43 months (interquartile range 6–104). The major pathogens were Staphylococcus sp. (n = 8, 44%), Enterococcus sp. (n = 4, 22%), and Aspergillus sp. (n = 3, 17%). Although eight patients (44%) had a surgical indication, it was only performed in three cases (17%). Three patients (17%) died during the first IE hospital admission. Conclusions: IE in HT recipients has specific characteristics. Valve involvement does not have a predominant location and non-valvular involvement is common. Three fifths have a nosocomial/health care-related origin. The major pathogens were staphylococci (44%), enterococci (22%), and Aspergillus (17%). In-hospital mortality was 17%. Highlights: Infective endocarditis in heart transplantation recipients has specific characteristics. There is no predominant valve location and non-valvular involvement is common. Three fifths have a nosocomial/health care-related origin. The major pathogens were staphylococci (44%), enterococci (22%), and Aspergillus (17%). Inhospital mortality was 17%.